El par cómico en la comedia temprana de Aristófanes y su pervivencia en "Lisístrata" - Schere, María Jimena (2017)
The notion of comic couple, understood as a conventional couple formed by two opposite and antagonistic characters, provides a fundamental key to understand Aristophanes' early comedy. This binary scheme is prevalent in the author's early extant comedies and will again be implemented in its more conventional form in Lisistrata. Its occurrence in Lisistrata is due, among other causes, to the fact that this play resumes the tone of satirical virulence present in the early plays and the controversy in favour of peace with Sparta, a theme which resonates in all of the author's early extant plays.